Evaluation of chitosan for blast disease suppression in MR 219 rice variety - Burhanudin, Farhana (2016)
Rice (Oryza sativa L.) from family Poaceae is the most important grain crop in Malaysia. Blast disease caused by the fungus Pyricularia oryzae is an important disease that affects rice production. Chitosan is a nontoxic biopolymer derived by deacetylation of chitin that shows antifungal effect against several pathogens hence, was successful in controlling diseases of several plants. However, chitosan is not known to suppress blast disease on MR 219 rice variety. Thus, this study was conducted, 1) to determine the effect of chitosan on mycelial growth of P. oryzae in vitro and 2) to assess the effect of different chitosan concentrations on disease development. Poison Agar Assay was used to test four chitosan concentrations (1, 2, 3 and 4%) and control in vitro. The radial growth was measured in the 14 days after inoculation resulted a highly significant difference among percent inhibition between all treatments. P. oryzae growth was totally inhibited at 4% concentration, however, the inhibiting effect was relatively low at 2 and 1% concentrations. The result showed a highly significant difference between all treatments where chitosan at 4% concentration caused a 19.40% disease incidence (DI) while 10.95% disease severity (DS) on rice plants compared to 84.08% DI and 71.15% DS in the control plants. Present results inferred that chitosan could act as an alternative natural compound in controlling blast disease on MR 219 rice variety.